2021
DOI: 10.1002/jclp.23289
|View full text |Cite
|
Sign up to set email alerts
|

The development of a self‐report scale to assess therapists' acceptance of telepsychotherapy

Abstract: Objective We aimed to develop a self‐report measure of therapist acceptance of telepsychotherapy based on the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. Methods Using a cross‐sectional survey design, 1265 therapists completed the UTAUT‐T, as well as additional questions. Results Confirmatory analysis indicated that the original UTAUT model did not fit the therapist context well. Exploratory factor analysis specified a better‐fitting five‐factor model, which showed good internal valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 64 publications
3
26
0
8
Order By: Relevance
“…Consistent with previous work, this study demonstrated the utility of the UTAUT for predicting the intention to use telephone and video technologies [ 12 , 16 , 22 , 24 ]. Specifically, performance expectancy was predictive of the intention to use both video and telephone services, while social influence and facilitating conditions were additionally predictive of the intention to use telephone services.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with previous work, this study demonstrated the utility of the UTAUT for predicting the intention to use telephone and video technologies [ 12 , 16 , 22 , 24 ]. Specifically, performance expectancy was predictive of the intention to use both video and telephone services, while social influence and facilitating conditions were additionally predictive of the intention to use telephone services.…”
Section: Discussionsupporting
confidence: 89%
“…The UTAUT-Therapist Version [ 22 ] assessed technology acceptance using 13 items based on the original UTAUT, on a scale of 1 (strongly disagree) to 5 (strongly agree), with subscales for performance expectancy, effort expectancy, social influence, and facilitating conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent empirical studies appear to confirm the multitude of teletherapy experiences; not better or worse per se, but different. Patient and therapist responses in international longitudinal surveys and in-depth interviews that we conducted (Aafjes-van Doorn, Aafjes-van Doorn, Békés, Luo, Prout, et al, 2021;Békés et al, 2021Békés et al, , 2022 suggest that the teletherapy process reflects a complex amalgamation of potentially helpful and unhelpful therapeutic experiences. Many therapists and patients reported difficulties with emotional connection, distractions, and privacy when they transitioned to teletherapy.…”
Section: Teletherapy Processmentioning
confidence: 99%
“…This suggests that besides the “objective” measurements of efficacy and effectiveness of teletherapy outcomes, it might also be important to examine therapists’ and patients’ attitudes towards teletherapy technology. Because no such measure existed for the use of teletherapy, we developed “attitudes towards teletherapy” scales based on the Unified Theory of Acceptance and Use of Technology -model to assess patients’ and therapists’ attitudes, concerns, and future intention of using teletherapy (UTAUT-T; Békés et al, 2021; UTAUT-P; Békés et al, 2022).…”
Section: Teletherapy Outcomes Definedmentioning
confidence: 99%